Short-term and long-term effects of Muslim fasting on lithium pharmacokinetics and renal function in bipolar disorder: a prospective observational study - Mohamed Abouzed; Abdullah Saleh Altuhayni; Salwa Rashed Alshammari; Mohamed Saad Almuqahhwi; Mohamed Elgernas; Abdulkarim Almazyadi; Abdullah Abdulaziz Alghuraymil; Yousef Ibrahim; Awwad Alenezy (International Journal of Bipolar Disorders)
Abstract This prospective observational study aimed to investigate the effects of Ramadan fasting on serum lithium levels, renal function, and electrolyte balance in patients with bipolar disorder undergoing lithium maintenance therapy. Conducted in Saudi Arabia, a region characterized by hot and arid climates (30–36 °C, 25% humidity during Ramadan 2024), the study included 250 participants divided into fasting (n = 131) and non-fasting (n = 119) groups. Serum lithium levels, renal function parameters (serum creatinine and estimated glomerular filtration rate), and electrolyte levels (sodium and potassium) were assessed at baseline, mid-Ramadan, one month post-Ramadan, and three months post-Ramadan. Statistical analyses included mixed-effects models, linear regression, and Wilcoxon rank-sum tests. The results indicate that Ramadan fasting did not significantly alter serum lithium levels, renal function, or electrolyte balance across all time points. These findings suggest that fasting during Ramadan can be safely practiced by patients with bipolar disorder receiving lithium therapy, provided they maintain adequate hydration and adhere to their prescribed medication regimen.